Reduction of Production Lead Time using Value Stream Mapping (VSM) Technique (Global Journals of Research in Engineering, 2017)
Value Stream Mapping (VSM) is a special type of flow chart that uses symbols known as "the language of Lean" to depict and improve the flow of inventory. In this research, process time and other unnecessary non value added activities of a battery manufacturing company have been reduced by using various lean manufacturing tools. The current situation is analyzed by showing a current state map. Then after using several lean tools, a future state value stream map has been showed. A different layout of the industry especially assembly section has been suggested. The layout of the assembly section is time wasting in current situation. They could reduce their overall production lead time as well as wastes by considering the suggestions about using lean tools and improved layout.